Earth System Science for Socio-Economic Benefits - Rajeevan, Madhavan Nair (IISER-M, 2017)
Earth System Science considers interactions between the Earth's spheres: Atmosphere, Hydrosphere, Cryospher, Lithosphere, and the Biosphere, as well as the impact of human societies on these components. The ministry of Earth Sciences has the mandate of providing weather, climate, ocean, coastal and seismological services for socio-economic benefits of the country. In the lecture, various scientific aspects of Earth System Science Services will be discussed. Major scientific the technological challenges in prediction of weather extremes, Climate Change, Earthquake Detection, Development of Ocean Technology, Exploration of Arctic and Antarctic et cetera will be elaborated. In addition, research opportunities being provided by the Ministry of Earth System Science will be also discussed.